ANALISIS ISI BUKU AJAR BAHASA ARAB (PENDEKATAN SAINTIFIK KURIKULUM 2013) KELAS I MADRASAH IBTIDAIYAH TERBITAN KEMENTERIAN AGAMA REPUBLIK INDONESIA 2014 - Hadi, Nurul (Ijaz Arabi Journal of Arabic Learning, 2018)
This research is aimed to reveal the appropriateness of Arabic textbook for the first grade of Islamic Elementary School/ Madrasah Ibtidaiyah (MI) published by Ministry of Religious Affairs of Indonesia in 2014 by using scientific approach. In analyzing this textbook, the researcher used library research and analyzed it by using content analysis and utilizing the theory of Arabic textbook arrangement by Nashir al-Ghali, besides that, the researcher also analyzed it by considering four aspects of Arabic textbook arrangement by Mackey which involves: selection, gradation, presentation, and repetition. And to identify either the textbook is appropriate or not to use based on 2013 curriculum standard, therefore, the researcher used regulation of Ministry of Religious Affairs (PMA) of Indonesia, Number: 0912 years 2013 about 2013 curriculum for madrasah of Islamic education and Arabic subjects as references. The result of the analysis on Arabic textbook with scientific approach of 2013 curriculum for the first grade of Islamic elementary school (Madrasah Ibtidaiyah) published by Ministry of Religious Affairs in 2014 showed that it was relevant and appropriate to be used to the students at the first grade of elementary level (Madrasah level) as material source that can support to achieve the goals of Arabic learning.